2021
DOI: 10.1111/plb.13276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperature and high humidity stress on physiology of cucumber at different leaf stages

Abstract: Low temperature (LT) and high humidity (HH) are important environmental factors in greenhouses and plastic tunnels during the cold season, as they hamper plant growth and development. Here, we studied the effect of LT (day/night: 9/5 °C, 25/18 °C as control) and HH (95%, 80% as control) on young cucumber plants at the 2, 4 or 6 leaf stages. LT+HH stress resulted in a decline in shoot, root and total fresh and dry weights, and decreased Pn, gs, Tr, Fv/Fm, qP, ETR and chlorophyll, and increased MDA, H2O2, O2‐, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 72 publications
4
19
0
Order By: Relevance
“…•− . Similar results were also found in lily [42] and cucumber [43]; as such, P. ostii can remove ROS produced under high-temperature stress by inducing the activity of antioxidant enzymes and reducing damage to the structure of the cell membrane, thus becoming better adapted to the external environment. However, studies on lettuce [44] showed that the peroxidase activity decreased with the development of high-temperature stress to varying degrees.…”
Section: Discussionsupporting
confidence: 78%
“…•− . Similar results were also found in lily [42] and cucumber [43]; as such, P. ostii can remove ROS produced under high-temperature stress by inducing the activity of antioxidant enzymes and reducing damage to the structure of the cell membrane, thus becoming better adapted to the external environment. However, studies on lettuce [44] showed that the peroxidase activity decreased with the development of high-temperature stress to varying degrees.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we show that MT application improves cucumber seedling growth under LT and HH stress by regulating seedling morphology and improving photosynthesis, antioxidant enzyme defense, and nutrient uptake. Consistent with our recent report ( Amin et al, 2021 ), LT and HH obstructed cucumber seedling growth by negatively affecting the plant morphological traits and biomass accumulation, and foliar application of MT effectively alleviated these inhibitory effects of LTHH stress. These results are also in agreement with the study of Li et al (2017) , which showed that the growth and biomass of plants reflect their sensitivity or resistance to abiotic stresses.…”
Section: Discussionsupporting
confidence: 92%
“…The reduction in morphological traits might be related to photosynthesis and the antioxidant defense system. LT and HH affect photosynthesis by impacting carbon (C) fixation and electron transport in thylakoids ( Amin et al, 2021 ). LT and HH damage photosynthesis by affecting energy production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations